2018
DOI: 10.21831/informasi.v48i1.19741
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Exploration on Terrorism Issues in Malaysia and Indonesia: The Case of the Wall Street Journal

Abstract: The symbiotic relationship between Islam and media is inevitable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Past studies on bilateral relationship between Malaysia and Indonesia showed that the media and media staff play important roles in mediating the conflict between the two countries. Scattered research on related issue examined media content, roles, framing and news constructions on specific issues such as Ambalat, cultural heritage (batik) and migrant labours (Adnan & Amri, 2016;Bharata & Nik Norma, 2019;Fauziah et al, 2018;Irwansyah, 2017;Mulharnetti, 2015;Rusdi et al, 2013;Wijayani et al, 2012;Wan Hassan et al, 2017) but lack of study on media staff newsroom routine. Media is perceived as powerful medium used by journalists and editors to either alleviate or reduce the rage among fellow nations by highlighting certain story angles repeatedly while excluding others.…”
Section: Problem Statementmentioning
confidence: 99%
“…Past studies on bilateral relationship between Malaysia and Indonesia showed that the media and media staff play important roles in mediating the conflict between the two countries. Scattered research on related issue examined media content, roles, framing and news constructions on specific issues such as Ambalat, cultural heritage (batik) and migrant labours (Adnan & Amri, 2016;Bharata & Nik Norma, 2019;Fauziah et al, 2018;Irwansyah, 2017;Mulharnetti, 2015;Rusdi et al, 2013;Wijayani et al, 2012;Wan Hassan et al, 2017) but lack of study on media staff newsroom routine. Media is perceived as powerful medium used by journalists and editors to either alleviate or reduce the rage among fellow nations by highlighting certain story angles repeatedly while excluding others.…”
Section: Problem Statementmentioning
confidence: 99%